Coping with loneliness through consumption. Issue 2 (14th November 2022) - Shrum, L. J.; Fumagalli, Elena; Lowrey, Tina M.
Abstract: Loneliness is a complex set of aversive feelings that arises when people perceive that their belongingness needs are not being met. Usually, these feelings of loneliness are temporary because people successfully cope with their loneliness by connecting with others. However, for some people, their attempts to cope with loneliness are unsuccessful, and their loneliness becomes chronic, which can have severe consequences for their mental and physical health. Understanding the causes and consequences of loneliness is critical for developing interventions to reduce loneliness, a need made more urgent by the dramatic rise in reported loneliness over the last few decades. In this review, we provide a synthesis of the research on how people cope with loneliness through consumption situations and the extent to which these coping strategies are successful. We also provide a discussion of how the marketplace has responded to the rapidly increasing levels of chronic loneliness worldwide. We conclude with an agenda for future research to answer both basic and applied research questions regarding the causes, consequences, and underlying processes of loneliness.